On Keeping Public Visual Fieldnotes As Reflexive Ethnographic Practice - Burkholder, Casey (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
These “Notes from the Field” describe one doctoral student’s public visual fieldnotes practice during her data collection for her dissertation. In the creation of a public digital space for participants and the public to engage with the fieldnotes through online comments and in-person conversations, this shifts the practice of keeping the researcher’s initial thoughts private and separate from the research participants. In an attempt to address a critique of her own Master’s work, and the potentially exclusionary practice of private fieldnotes writing in participatory research, the piece raises questions about positionality and ethical concerns in relation to a digital archive of public visual fieldnotes as reflexive ethnographic practice.